A General Financial Transactions Tax. Motives, Effects and Implementation According to the Proposal of the European Commission - Stephan Schulmeister (Austrian Institute of Economic Research (WIFO), 2014)
The paper summarises at first the main arguments in favour and against a FTT and provides empirical evidence about the movements of the most important asset prices. It is shown that their long swings result from the accumulation of extremely short-term price runs over time. Therefore a (very) small FTT - between 0.1 and 0.01 percent - would mitigate price volatility not only over the short run but also over the long run. The subsequent section discusses the most important implementation issues if only a group of 11 EU member countries introduces this tax (without the UK). If London subsidiaries of banks established in one of the FTT countries are treated as part of their parent company, overall FTT revenues of the 11 FTT countries are estimated at 65.8 billion, if London subsidiaries are treated as British financial institutions, tax revenues would amount to only 28.3 billion.
Keywords: 330; Tobinsteuer; Steuerreform; Steuerwirkung; EU-Staaten